Neuroendocrine Carcinoma of the Stomach: A Case Study - Keisuke Kubota; Akihiro Okada; Junko Kuroda; Masashi Yoshida; Keiichiro Ohta; Miki Adachi; Masayuki Itabashi; Yoshiyuki Osamura; Masaki Kitajima (Case Reports in Medicine)
Gastric neuroendocrine carcinomas are rare and have a poor prognosis, and the diagnostic criteria for this disease have recently changed. We herein report a case of sporadic gastric neuroendocrine carcinoma. A 75-year-old man was referred to our hospital with epigastric pain. Endoscopic examination revealed a localized ulcerative lesion (diameter, 4 cm) at the upper stomach. The diagnosis on biopsy was neuroendocrine carcinoma. Total gastrectomy with D2 lymphadenectomy, splenectomy, and cholecystectomy was performed. Pathologically, the tumor infiltrated the subserosal layer, and 6/49 lymph nodes were involved. The tumor was uniform in shape and arranged in a rosette-like structure to form solid nests, with medium-sized, round-to-cuboid-shaped tumor cells and intense mitosis 46/10 HPF. It was positive for synaptophysin and chromogranin A, and the Ki-67 labeling index was 70–80%. The diagnosis of neuroendocrine carcinoma was made according to the WHO 2010 criteria. The patient was followed up for three years without recurrence.